Coach and player attitudes to injury in youth sport. (July 2018) - Whatman, Chris; Walters, Simon; Schluter, Philip
Abstract: Objectives: To investigate coach and player attitudes to injury in New Zealand (NZ) secondary school sport. Design: Cross-sectional survey Setting: Secondary school sport. Participants: Secondary school coaches and players. Main outcome measures: Responses to a survey of injury attitudes. The survey was distributed in electronic and paper-based form to secondary school coaches and players across three sporting organisations. Coaches' uptake of injury prevention training and whether they had first aid qualifications was also elicited. Results: 117 coaches and 226 players from netball, football and basketball participated. The majority of coaches surveyed (n = 82, 70%) reported having a coaching qualification and 72 (62%) had completed a sport related first aid/injury prevention programme. Overall, 196 players (87%) reported hiding an injury to continue playing, and 102 coaches (87%) and 205 players (91%) had witnessed injured players play on. Approximately 50% of players and coaches had seen players put under pressure to play when injured. A lack of knowledge, the desire to win, and not letting the team down were key reasons given for the behaviour reported. Conclusions: The observed prevalence of players playing on when injured and associated attitudes to secondary school sport injuries demands further investigation. Highlights: Over 80% of players reported hiding an injury to continue playing. Over 80% or coaches and players had witnessed injured players play on. A change in behaviour is needed in youth sport to ensure injured players do not continue playing. Reduced emphasis on winning, changes to interchange rules and further education of coaches and players should be considered.